THE PRINCIPLE OF THE USEFULNESS OF A WAQF OBJECT IN THE PERSPECTIVE OF NAZHIR PROFESSIONALISM BASED ON LAW NUMBER 41 YEAR 2004 ABOUT WAQF IN SUB-DISTRICT CIAWI AND SUB-DISTRICT MEGAMENDUNG BOGOR - Siti Sulastri; Ani Yumarni; Sudiman Sihotang (JURNAL HUKUM DE'RECHTSSTAAT, 2018)
Realizing the expediency principle of waqf property, one of the efforts that be able to conducted is selecting and appointing nazhir that is conform the criteria and standards of professional nazhir competence. The purpose of study is to determine the criteria and professional nazhir competence in order to realize the expediency principle to assets of waqf in Ciawi and Megamendung district as well as to know the legal effect on waqf asset if nazhir not professional in managing and developing it. The approach method used in this research is sociological juridical (empirical), the law as a symptom of society, as a social institution or behavior that is pattern. Technical data collection used is through observation method, and interview method (interview). Based on results of research conducted by the author that the criteria and standards of professional nazhir competence is proficient, reasonable, law waqf understanding both Syariah and law, behaved as has been exemplified by the prophet Muhammad SAW namely sidiq, amanah, fathanah, tabligh, and possess skills and creativity not only in the field of syariah but law field, management and business. The legal consequences of the unmanaged asset of waqf in accordance to the legislation are the objects of waqf being displaced so that the management and its development can be taken over by the Badan Wakaf Indonesia, accordance to applicable laws and regulations